1997
DOI: 10.1128/jb.179.10.3270-3276.1997
|View full text |Cite
|
Sign up to set email alerts
|

The actinomycete Thermobispora bispora contains two distinct types of transcriptionally active 16S rRNA genes

Abstract: Here we present the first description of the presence of two distinct types of 16S rRNA genes in the genome of a (eu)bacterium, Thermobispora bispora. We cloned and determined the nucleotide sequences of all four rRNA operons of T. bispora. Sequence comparisons revealed that the genome of T. bispora contains two distinct types of 16S rRNA genes, each type consisting of two identical or nearly identical copies, and three identical copies of the 23S RNA gene. The nucleotide sequences of the two types of 16S rRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
95
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(100 citation statements)
references
References 37 publications
3
95
0
2
Order By: Relevance
“…These two properties of rRNA molecules underscore the high possibility of the exchange of individual hairpins without damaging effect on the proper function of a ribosome. This view is supported by reports that an organism may have distinct types of rRNA genes with high levels of base variations throughout the entire gene (Gunderson et al, 1987 ;Mylvaganam & Dennis, 1992 ;Carranza et al, 1996 ;Wang et al, 1997 ;. Niebel et al (1987) demonstrated that the rRNA cistrons from Proteus vulgaris were expressed and the products correctly processed and assembled into ribosomes when transformed into E. coli.…”
Section: Discussionsupporting
confidence: 56%
“…These two properties of rRNA molecules underscore the high possibility of the exchange of individual hairpins without damaging effect on the proper function of a ribosome. This view is supported by reports that an organism may have distinct types of rRNA genes with high levels of base variations throughout the entire gene (Gunderson et al, 1987 ;Mylvaganam & Dennis, 1992 ;Carranza et al, 1996 ;Wang et al, 1997 ;. Niebel et al (1987) demonstrated that the rRNA cistrons from Proteus vulgaris were expressed and the products correctly processed and assembled into ribosomes when transformed into E. coli.…”
Section: Discussionsupporting
confidence: 56%
“…We used PCR products directly as templates for sequencing, whilst Tan et al (1997) used a cloned PCR fragment. This difference in methodology may explain the disparity of the results since Mesorhizobiurn harbours two 16s rRNA genes (van Berkum et al, 1998b) and they may show sequence heterogeneity (Cilia et al, 1996;Wang et al, 1997).…”
Section: Phylogeny Of the Isolatesmentioning
confidence: 69%
“…A possible source of error that would produce bush-like phylogenies is intraspecies variation in the rRNA operon sequences, and it has been suggested that sequences from single operons cannot adequately represent taxa (7). A few examples of intraspecies rRNA operon sequence variation greater than 3% have been reported (29,52,57); however, a compilation of data from the genome sequences indicates that such high heterogeneity is exceptional (17). Our results confirm previous observations that the Bacteroides and Prevotella group constitutes the largest fraction of gram-negative bacteria in the porcine GI tract.…”
Section: Discussionmentioning
confidence: 99%